The Distillation of National Crime Data into A Plan for Elderly Fraud Prevention: A Quantitative and Qualitative Analysis of U.S. Postal Inspection Service Cases of Fraud against the Elderly - Rebovich, Donald J. (Victims & offenders, 2021)
The following article represents the product of a research study funded by the United States Postal Inspection Service (USPIS) and conducted by researchers from the Identity Management and Information Protection Center (CIMIP) of Utica College. The study focuses on frauds committed against victims aged 55 years and older. The primary objective was to uncover as much key empirical information on characteristics of victims of elderly fraud, those who commit these crimes, and the methods they employ to commit these fraudulent acts. For this study, researchers were afforded the opportunity to examine criminal case investigation data from the USPIS national criminal case database on elderly frauds. The data that supplies the foundation for this study relies on information from criminal case investigators transposed to a national database reflecting critical characteristics of cases of fraud against the elderly. Recommendations are offered as to how the analysis of this information can be beneficial in the development of effective public awareness campaigns for helping to prevent elderly fraud victimization.